2021
DOI: 10.26043/giso.2021.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerabilitätserfahrungen und die Erarbeitung von Agency: Ankommensprozesse junger Geflüchteter

Abstract: Unbegleitete minderjährige Geflüchtete befinden sich nach ihrer Ankunft in Europa in prekären Lebenssituationen, die mit Vulnerabilitätserfahrungen einhergehen, die sie gleichzeitig bearbeiten und bewältigen. Denn mit der Ankunft ist zwar die Fluchtmigration beendet, doch angekommen sind die Jugendlichen noch nicht. Wie gestalten Jugendliche den Prozess des Ankommens, und welche Formen von Agency erarbeiten sie sich unter den jeweiligen sozialen Bedingungen? Diese Fragen fokussiert der Beitrag und rekonstruier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…They have also discussed the lack of child protection standards and sociopedagogical support in refugee centres (Mey et al, 2019), and identified challenges in relation to the accommodation and support of unaccompanied minor refugees (Rieker et al, 2020). In this context researchers have also investigated experiences of external control, and unreasonable expectations associated with demands for integration and, for example, foster family placements (Mörgen & Rieker, 2021a;2021b). It is only now 24 that scholars are studying the children of Italian guest workers, and there has been little research into illegal migrants as care-workers in Switzerland (Knoll et al, 2012).…”
Section: Current Debatesmentioning
confidence: 99%
“…They have also discussed the lack of child protection standards and sociopedagogical support in refugee centres (Mey et al, 2019), and identified challenges in relation to the accommodation and support of unaccompanied minor refugees (Rieker et al, 2020). In this context researchers have also investigated experiences of external control, and unreasonable expectations associated with demands for integration and, for example, foster family placements (Mörgen & Rieker, 2021a;2021b). It is only now 24 that scholars are studying the children of Italian guest workers, and there has been little research into illegal migrants as care-workers in Switzerland (Knoll et al, 2012).…”
Section: Current Debatesmentioning
confidence: 99%